Application of adaptive laboratory evolution to overcome a flux limitation in an Escherichia coli production strain. Issue 6 (8th March 2018) - Tokuyama, Kento; Toya, Yoshihiro; Horinouchi, Takaaki; Furusawa, Chikara; Matsuda, Fumio; Shimizu, Hiroshi
Abstract: Gene deletion strategies using flux balance analysis (FBA) have improved the growth‐coupled production of various compounds. However, the productivities were often below the expectation because the cells failed to adapt to these genetic perturbations. Here, we demonstrate the productivity of the succinate of the designed gene deletion strain was improved by adaptive laboratory evolution (ALE). Although FBA predicted deletions of adhE‐pykAF‐gldA‐pflB lead to produce succinate from glycerol with a yield of 0.45 C‐mol/C‐mol, the knockout mutant did not produce only 0.08 C‐mol/Cmol, experimentally. After the ALE experiments, the highest succinate yield of an evolved strain reached to the expected value. Genome sequencing analysis revealed all evolved strains possessed novel mutations in ppc of I829S or R849S. In vitro enzymatic assay and metabolic profiling analysis revealed that these mutations desensitizing an allosteric inhibition by L‐aspartate and improved the flux through Ppc, while the activity of Ppc in the unevolved strain was tightly regulated by L‐aspartate. These result demonstrated that the evolved strains achieved the improvement of succinate production by expanding the flux space of Ppc, realizing the predicted metabolic state by FBA. Abstract : This study unveiled the reason why engineered strains based on in silico design by flux balance analysis (FBA) couldn't reach to the optimal state for growth‐coupled productions. In succinate production by Escherichia coli, allosteric inhibition of phosphoenolpyruvate carboxylase (Ppc) by L‐aspartate diminished a flux space of actual metabolic network and thereby hampered the growth‐coupled succinate production. Adaptive laboratory evolution overcame the constraint with introducing mutations desensitizing L‐aspartate inhibition to Ppc, and led to enhanced succinate production as predicted by FBA..